Dennis Pardee, Ritual and Cult at Ugarit - Vita, Juan-Pablo (Syria, 2009)
The work includes sixty Ugaritic texts, transcribed and translated, which according to the author (p. 1) “deal with the everyday contacts between the Ugaritians and their deities ... The texts fall into two primary categories: those that reflect directly the sacrificial cult as carried out in the various sanctuaries of the city of Ugarit (sections I‑VII) and those that witness the infusion of ritual practice into life outside the sanctuary itself (sections VIII‑XII)”. Along with texts which a...